American and Australian family experiences while receiving a diagnosis or having treatment for idiopathic toe walking: a qualitative study. Issue 9 (2nd September 2020) - Williams, Cylie; Robson, Kristy; Pacey, Verity; Gray, Kelly
Abstract : Objective: To understand parent journeys while navigating diagnosis, assessment or treatment of their children with idiopathic toe walking (ITW). Design: Mixed methods qualitative study: analyses of survey data from the measure of processes of care-20 (MPOC-20) and semistructured interviews were analysed with an interpretative phenomenological analysis approach. Trustworthiness of data was achieved through member checking, researcher triangulation, reflexivity and transferability and comparison with the MPOC-20 results. Setting: USA and Australia. Participants: Parents of children diagnosed with ITW who had seen more than one health professional during their care and lived in Australia or the USA. Results: Ten parents of children aged between 3 and 13 years and diagnosed with ITW participated. Parents described complex themes relating to their journeys. The themes relating to their journeys were: (1) riding the rollercoaster of diagnosis; (2) navigating the treatment options and (3) supporting parents in the journey. Each theme was supported by parent quotes about their experiences. Challenges were not localised to one country, in spite of vastly different healthcare systems. Conclusions: These findings create opportunities for an international approach to education, treatment recommendations and outcome measures to improve patient and parent experiences. Health professionals should consider the impact on parents in navigating between health professionals when provided with a diagnosis which can have variable outcomes and varied treatment options.